A KAP study on snake bite among the rural population in Tirunelveli district - G., Krishnaleela; Meena M., Selva; A., Praveena Daya (International Journal Of Community Medicine And Public Health, 2018)
Background: India has 236 species of snakes of which 13 species are poisonous. Most of the Indian population are in rural area and they are poorly informed about the snake bite. They waste their vital time by reporting to traditional healers and taking inappropriate first aid. So the present study is done to determine the knowledge, attitude and practice on snake bite among the rural population of Tirunelveli district. Methods: A cross–sectional study was done in rural area of Tirunelveli district. 200 adults were included in our study. Data on knowledge, attitude and practice were collected by the trained personnel using a predesigned structured questionnaire for the period of three months from June 2017 to August 2017. Results: 60.5% of the study population can’t identify the snake. 54% of them had knowledge on availability of ASV.62% of study subjects had no knowledge on complications of snake bite. It was also found that most of them had practice of tying tourniquet above the site of bite, sucking blood from the site, washing with soap and water. 62.5% preferred hospital treatment for snake bite only 12% preferred traditional practices and 59.5% believed that ASV is effective. Conclusions: Knowledge on identification of snake and on ASV is low and still some people follow harmful practices like taking to traditional healers and applying native medicine so steps must be taken to improve their knowledge and to prevent harmful practices.